Energy and Fat Intake for Preterm Infants Fed Donor Milk Is Significantly Impacted by Enteral Feeding Method. Issue 1 (2nd August 2018) - Castro, Marina; Asbury, Michelle; Shama, Sara; Stone, Debbie; Yoon, Eugene W.; O'Connor, Deborah L.; Unger, Sharon
Abstract: Background : Pasteurized donor milk is the recommended supplement for preterm infants when mother's milk volumes are insufficient. Compared with mother's milk, the macronutrient content of donor milk is thought to be lower due to pasteurization and additional container changes during processing. Given that poor growth is concerning for preterm infants, it is important to understand how processing and feeding methods influence the nutrition composition of donor milk feeds. The research aim of this study was to determine the effects of pasteurization and feeding method on the macronutrient and energy composition of donor milk. Ten donor milk pools were pasteurized, prepared according to neonatal practices, and infused through nasogastric tubes to simulate 4 feeding methods: bolus, 30 minutes, 60 minutes, and continuous feeding over 4 hours. Macronutrient concentrations were assessed after pasteurization, preparation, and each feeding method using a mid‐infrared human milk analyzer. Results : There were no significant decreases in macronutrient content after pasteurization or bolus feeding. However, energy and fat losses increased with slower infusion rates. After continuous feeding for 4 hours, energy and fat concentrations decreased by a mean of 17.3 (15.8–18.8) kcal/dL and 2.08 (1.90–2.25) g/dL ( P < .0001), respectively. Conclusions : Pasteurization did not significantly reduce donor milk macronutrient and energy content; however, feeding method significantly impacted the final delivery of energy and fat.